EP07 Synovitis-acne-pustulosis-hyperostosis-osteitis syndrome: diagnosis via chest radiograph. (20th April 2020) - Anandan, Lavanya; Mukhtar, Mohsin; Walker, Miny; Kinderlerer, Anne; Halai, Kapil
Abstract: Background: Synovitis-acne-pustulosis-hyperostosis-osteitis (SAPHO) is a rare inflammatory disorder that usually manifests with dermatological and osteoarticular features. However a significant proportion, 40% of patients, present solely with osteoarticular features. We present a case of an Eritrean female, presenting with no cutaneous features, who was diagnosed with SAPHO following classical radiological features initially identified on a chest radiograph. Methods: A literature review was conducted using rheumatological and radiological articles, searching for the term SAPHO syndrome and related key words. Anecdotal evidence was used from one patient diagnosed with SAPHO at this trust. Results: A middle-aged Eritrean female presented to A&E with a skin rash following naproxen use for chronic right shoulder pain. Subsequent skin biopsy demonstrated a leucocytoclastic vasculitis and dermatology diagnosed this as an adverse reaction to naproxen. Due to shoulder pain and a raised ESR and rheumatoid factor, she was referred to rheumatology. She also underwent a chest X-ray for atypical chest pain in the community which demonstrated an ill-defined area in the right apex. A dedicated apical lordotic view showed unilateral hyperostosis of the right medial clavicle and first rib, raising the suspicion of SAPHO. A CT chest and MRI clavicle were organised to further characterise the findings and exclude other diagnoses, such as infection. CT demonstrated expansion, sclerosis, cortical thickening, periostitis and partial fusion of the right sternoclavicular joint. MRI showed bony expansion of the medial clavicle, manubrium and proximal sternum with bone marrow oedema and partial fusion at the sternoclavicular joint. Whilst the radiological findings were classical for SAPHO, the lack of skin features, and few clinical symptoms did not support the diagnosis. Although there were no symptoms of tuberculosis (TB) and the initial elispot result was indeterminate, given the rarity of SAPHO and the patient's country of origin it was felt necessary to exclude TB. The case was subsequently discussed amongst rheumatology, respiratory and radiology teams with consultation from a SAPHO expert. On re-examination, the radiological findings were not felt to suggest TB, and in the absence of a relevant clinical history and multiple negative IGRA tests, TB was excluded. Conclusion: SAPHO syndrome is a rare condition affecting the skin, joints and bones. 60% of patients diagnosed with SAPHO present with cutaneous and osteoarticular features. However, the osteoarticular features of SAPHO remain the key clinical findings and patients can present with these features alone. Classical features of SAPHO on plain radiographs include a bull's head appearance of the sternoclavicular region, sclerotic lesions, periosteal changes, hyperostosis and osteitis. 40% of patients present solely with osteoarticular features and this presents a diagnostic challenge with a wide differential list. Such cases require the input of a multi-disciplinary team before considering treatment. Disclosures: L. Anandan None. M. Mukhtar None. M. Walker None. A. Kinderlerer None. K. Halai None.